1995
DOI: 10.1111/j.1479-828x.1995.tb02168.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotoxicosis in Pregnancy Presenting as Pancytopenia

Abstract: Delay in diagnosis of thyroid disease can result in morbidity and mortality. Thyroid disorders are not uncommon in the reproductive age group and therefore in pregnancy; recognition of both the common and the more unusual manifestations will optimize outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…Previous studies have reported the prevalence of neutropenia in hyperthyroidism to be between 15% and 30% . In addition, small studies and a few case reports have also shown normalization of neutrophil counts with normalization of thyroid function . These reports were based on small numbers of patients and did not assess other factors associated with neutrophil counts in hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the prevalence of neutropenia in hyperthyroidism to be between 15% and 30% . In addition, small studies and a few case reports have also shown normalization of neutrophil counts with normalization of thyroid function . These reports were based on small numbers of patients and did not assess other factors associated with neutrophil counts in hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In addition, small studies and a few case reports have also shown normalization of neutrophil counts with normalization of thyroid function. 7,[13][14][15][16] These reports were based on small numbers of patients and did not assess other factors associated with neutrophil counts in hyperthyroidism. Our study of neutrophil counts has collected data in a prospective and systematic manner in patients at baseline, prior to ATD therapy, and after achieving euthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…True hyperthyroidism is rarely complicated with pancytopenia; to the best of our knowledge, only 10 cases including our current case have been reported (Table ) . In our case, a blood laboratory examination performed at 9 GW (at admission due to severe hyperemesis gravidarum) detected pancytopenia, and subsequent investigation of the causes of the patient's pancytopenia resulted in the diagnosis of hyperthyroidism.…”
Section: Discussionmentioning
confidence: 62%
“…Pancytopenia is a complication of hyperthyroidism, but it is very rare. Although hyperemesis gravidarum is often associated with the occurrence of transient hyperthyroidism, to the best of our knowledge, no cases of transient hyperthyroidism during pregnancy complicated with pancytopenia have been reported. To rule out the possibility of transient hyperthyroidism, we measured the patient's TSH receptor antibody level and found that it was significantly increased, which resulted in a diagnosis of hidden hyperthyroidism.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation